Atlatl Dart Velocity: Accurate Measurements and Implications for Paleoindian and Archaic Archaeology. (3rd April 2017) - Whittaker, John C.; Pettigrew, Devin B.; Grohsmeyer, Ryan J.
ABSTRACT: Thrusting spears, hand-thrown javelins, and atlatls are all suggested as weapons used by Paleo hunters to bring down Pleistocene megafauna. Before we can distinguish between weapons in archaeological contexts, or compare their effects, we need accurate measurements of performance characteristics. Velocity directly influences momentum and kinetic energy and thus the damage a projectile can do, but accurate measurements of atlatl dart velocity are scarce. Measuring dart velocity requires naturalistic experiments involving human throwers. We measured numerous well-practiced individuals using a variety of atlatl equipment, comparing radar gun, film, and chronograph measurements of dart velocity. The atlatls used in hunting and warfare probably did not accelerate darts much beyond 35 m/s (78 mph). We evaluate Hutchings' use of fracture velocity measurements on stone points to distinguish Paleoindian projectile systems, which seems promising but needs better experimental support, and we use kinetic energy and momentum calculations for various projectiles to consider the shift from atlatls to bows in the Southwest.